Dark witch / [large type] - Roberts, Nora (Roberts, Nora. Cousins O'Dwyer trilogy, 2013)
"Iona Sheehan grew up craving devotion and acceptance. From her maternal grandmother, she learned where to find both: County Mao, Ireland. Iona arrives in Ireland with nothing but her Nan's directions, an unfailingly optimistic attitude, and an innate talent with horses. There she finds her cousins, Branna and Connor O'Dwyer, and they invite her into their lives. When Iona lands a job at the local stables, she meets the owner, Boyle McGrath. Iona realizes that here she can live her life as she wants, even if that means falling for Boyle. But an ancient evil has wound its way around Iona's family tree and must be defeated."--